TINJAUAN MODERASI BERAGAMA TERHADAP TERJEMAHAN DAN TAFSIR RINGKAS KEMENTERIAN AGAMA ATAS WAḌRIBŪHUNNA - Misbahul Huda; Masyhari; Moch. Farich Alfani; Syafik Muhammad (EL-ADABI : Jurnal Studi Islam, 2025)
Domestic violence committed in the name of religion often originates from literal and decontextualized interpretations of the phrase waḍribūhunna in QS. al-Nisā’ [4]:34. This study examines the evolution of the official Indonesian Ministry of Religious Affairs (Kemenag) translations and interpretations of this phrase through the lens of religious moderation (wasathiyyah). Using qualitative library research with content and comparative analysis, the study reviews four official Kemenag publications: Al-Qur’an dan Terjemahnya (1971), the Revised Translation (2019), Al-Qur’an dan Tafsirnya (2011), and Tafsir Ringkas (2016). The findings demonstrate a significant shift from earlier literal-textual renderings toward a more contextual and moderate interpretive approach in later editions. This shift is evident in the inclusion of clarifying phrases such as “(if necessary)” and “(in a non-harmful manner),” which reposition the command as symbolic and strictly a last resort. Such reinterpretation reflects the growing application of key moderation principles tawassuṭ (middle path), tawāzun (balance), i‘tidāl (justice), and sadd al-dzarī‘ah (preventing harm). The study concludes that integrating moderation-based semantic approaches in translating Qur’anic legal verses is essential to prevent their misuse as religious justification for violence. Moreover, state-authorized translations play a strategic role in safeguarding vulnerable groups and projecting Islam in Indonesia as a compassionate and peace-oriented tradition.